2014
DOI: 10.1063/1.4867288
|View full text |Cite
|
Sign up to set email alerts
|

Proton-bound dimers of nitrogen heterocyclic molecules: Substituent effects on the structures and binding energies of homodimers of diazine, triazine, and fluoropyridine

Abstract: The bonding energies of proton-bound homodimers BH(+)B were measured by ion mobility equilibrium studies and calculated at the DFT B3LYP/6-311++G** level, for a series of nitrogen heterocyclic molecules (B) with electron-withdrawing in-ring N and on-ring F substituents. The binding energies (ΔH°(dissoc)) of the proton-bound dimers (BH(+)B) vary significantly, from 29.7 to 18.1 kcal/mol, decreasing linearly with decreasing the proton affinity of the monomer (B). This trend differs significantly from the constan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Auguring well for our own data above, these authors found good agreement between their experimental measurements and calculated data. Prior work has extended as well to radical cation dimers where both experimental and calculated data have shown that both stacked and perpendicular arrangements can occur in homo and heterodimers of aromatics. These geometries can at times be quite competitive in terms of energy, as for example in the case of the naphthalene/benzene dimer.…”
Section: Discussionmentioning
confidence: 99%
“…Auguring well for our own data above, these authors found good agreement between their experimental measurements and calculated data. Prior work has extended as well to radical cation dimers where both experimental and calculated data have shown that both stacked and perpendicular arrangements can occur in homo and heterodimers of aromatics. These geometries can at times be quite competitive in terms of energy, as for example in the case of the naphthalene/benzene dimer.…”
Section: Discussionmentioning
confidence: 99%
“…It has to be mentioned, however, that both monomer and dimer signals indicate the presence of protonated species, which could contribute to the dimerisation preference. 14 For a better understanding of this assembly tendency, we investigated the agglomeration behaviour of unprotonated species via molecular dynamics (MD) simulations starting from 100 individual molecules in a volume corresponding to 10 À4 M concentration (for details, see ESI †). After several ns-long simulations at 200 K we found a high probability for the formation of supramolecular dimers (Fig.…”
mentioning
confidence: 99%
“…The mechanisms of the nitrogen incorporation in the PAH ions are important in understanding the ion chemistry in a nitrogen rich atmosphere such as that of Titan [9,13,[58][59][60][61]. DFT calculations indicate that substitution of a carbon atom with nitrogen in the benzene cation ring leads to lowering or eliminating the barrier to the acetylene addition [46][47][48][49][50][51][52][53][54]. These predictions are experimentally verified by the observation of fast sequential reactions of acetylene with the pyridine and pyrimidine cations [26].…”
Section: Comparison With the Reactions Of The Pyridine And Pyrimidinementioning
confidence: 84%
“…1). The details of the instrument can be found in several publications [25,26,38,47] and only a brief description of the experimental procedure is given here. The molecular ions benzonitrile (C 7 H 5 N + , m/z 103), phenylacetylene (C 8 H 6 + , m/z 102), or styrene (C 8 H 8 + , m/z 104) were generated by 50 eV EI ionization following the supersonic beam expansion of the corresponding vapor mixture consisting of 0.1-0.2% of the organic vapor (benzonitrile, Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation